Pretransplant 4β‐hydroxycholesterol does not predict tacrolimus exposure or dose requirements during the first days after kidney transplantation. (14th July 2017) - Vanhove, Thomas; Hasan, Mahmoud; Annaert, Pieter; Oswald, Stefan; Kuypers, Dirk R. J.
Abstract : Aims: The CYP3A metric 4β‐hydroxycholesterol (4βOHC) has been shown to correlate with tacrolimus steady‐state apparent oral clearance (CL/F). Recently, pretransplant 4βOHC was shown not to predict tacrolimus CL/F after transplantation in a cohort of renal recipients ( n  = 79). The goal of the current study was determine whether these findings could be validated in a substantially larger cohort. Methods: In a retrospective analysis of 279 renal recipients, tacrolimus trough concentrations (C0), daily dose, haematocrit and other relevant covariates were registered every day for the first 14 days after transplantation. 4βOHC and cholesterol were quantified on plasma collected immediately pretransplant using liquid chromatography tandem‐mass spectrometry. Patients were genotyped for CYP3A5*1 and CYP3A4*22 . Results: A total of 3551 tacrolimus C0 concentrations were registered. In a linear mixed model for the 14‐day period, determinants of tacrolimus C0 were CYP3A5 genotype, haematocrit, age and weight (overall R 2  = 0.179). Determinants of daily dose were CYP3A5 genotype, age, methylprednisolone dose, tacrolimus formulation, ALT and estimated glomerular filtration rate (overall R 2  = 0.242). Considering each of the first 5 days separately, 4βOHC had a limited effect on tacrolimus C0 on day 3 only (−1.00 ng ml −1 per ln, P  = 0.035) but not on any other day, and no effect on dose or C0/dose. During the first 5 days, haematocrit and age, which were previously established as determinants of tacrolimus disposition under steady‐state conditions, never explained more than 17.7% of between‐subject variability in tacrolimus C0/dose. Conclusions: The CYP3A metric 4βOHC cannot be used to predict tacrolimus dose requirements in the first days after transplantation.